Effect of FMA Dose and Cytokinin Concentration on the Growth and Yield of Jatropha Curcas L.) - Khofiyya, Nida; Budiasih, Budiasih; Noertjahyani, Noertjahyani; Indriana, Kovertina Rakhmi; Amalia, Lia (Institute of Computer Science (IOCS), 2022)
Jatropha curcas L.) is one of the vegetation that produces energy and is often used as biodiesel in an effort to reduce the use of fossil energy that has limited reserves, cannot be renewed (Unrenewable) and has emissions of combustion gases (pollutants) that cause environmental impacts such as the greenhouse gas effect and affect air quality. This experiment was carried out at the Experimental Garden of the Faculty of Agriculture, Winaya Mukti University, Sumedang Regency. The altitude of the place is 850 m above sea level. The trial time is from September to October 2022. The purpose of the experiment was to study the interaction between FMA dosing and cytokinin concentration against increasing growth of IP-3P cultivar jatropha plants in medium plains and obtain the best FMA dosing treatment and cytokinin concentration on IP-3P cultivar jatropha plant growth in medium plains. The study used a randomized group design (RAK) factorial pattern, which consisted of two factors, namely FMA dose with levels: 0 g, 5 g, 10 g, 15 g, 20 g and cytokinin concentrations with levels: 0 MgL-1, 150 MgL-1, 300 MgL-1, 450 MgL-1, 600 MgL-1. Each treatment factor consists of 5 levels. Each treatment is repeated twice, then the total amount of 5 x 5 x 2 = 50 plots. The results of the experiment showed an interaction between FMA dosing and cytokinin concentration on the constraint parameters of the stomata, the number of leaves and the diameter of the stem. It was found that the treatment of FMA dose level f3 (15 grams) gave the best results on the parameters of mycorrhizal colonization, leaf chlorophyll, plant height, number of leaves, number of lateral branches, and root weight + FMA. In the treatment of cytokinin concentration level s3 gave the best results on the parameters of mycorrhizal colonization, leaf chlorophyll, as well as the number of leaves